A COMPARATIVE ANALYSIS OF ELECTRONIC AND TRADITIONAL LEARNING - Denić, Nebojša; Zejnelagić, Merdan; Kontrec, Nataša (Bulletin of Natural Sciences Research, 2018)
Modern way of living and functioning of human society requires a new principle of decision making and adjusting to contemporary living needs. In times when humans have perfected the contemporary living needs with their technological achievements yet another disadvantage among those needs has appeared. Studying possibilities and adjusting to educational requirements have hardly made any progress in years. Traditional learning methods are implemented by means of book, pencil and paper, as was the case thousands of years ago, supporting functioning of human society. This paper, based on researches founded on implementation of educational software and researches founded on postulates of implementation of frontal education and summarizing related specialized literature from this area, will set forth possibilities for implementation of information and communications technologies (ICT) and educational software in teaching. The results of this research indicate that the students who were using electronic methods of learning in combination with traditional learning had become more motivated, skilled and interested in a new way of thinking that activates all senses in order to form their intellectual personality.